2011
DOI: 10.1590/s1807-59322011000800015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multidisciplinar cognitive rehabilitation program for patients with mild Alzheimer's disease

Abstract: OBJECTIVE:To evaluate the effects of a multidisciplinary rehabilitation program on cognition, quality of life, and neuropsychiatric symptoms in patients with mild Alzheimer's disease.METHOD:The present study was a single-blind, controlled study that was conducted at a university-based day-hospital memory facility. The study included 25 Alzheimer's patients and their caregivers and involved a 12-week stimulation and psychoeducational program. The comparison group consisted of 16 Alzheimer's patients in waiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
27

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 34 publications
(31 reference statements)
3
78
1
27
Order By: Relevance
“…Stability of scores or an attenuation of decline was reported in six group studies (Arkin, 2007;Graessel et al, 2011;Ibarria et al, 2016;La Rue et al, 2015;Maci et al, 2012;Viola et al, 2011). Two group studies, Serda`i Ferrer and del Table 6.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Stability of scores or an attenuation of decline was reported in six group studies (Arkin, 2007;Graessel et al, 2011;Ibarria et al, 2016;La Rue et al, 2015;Maci et al, 2012;Viola et al, 2011). Two group studies, Serda`i Ferrer and del Table 6.…”
Section: Resultsmentioning
confidence: 92%
“…For instance, the CDR global score has been recommended as a staging or impression of change outcome measure in future studies (Webster et al, 2017). The Short Cognitive Test (SKT) has also been known to be 'more sensitive to subtle changes' than the MMSE as it is a 'more comprehensive cognitive assessment battery and takes account processing speed and response accuracy' (Viola et al, 2011). Study design -Pharmacology and the Naturalistic.…”
mentioning
confidence: 99%
“…With the application of this program, the patient's neuropsychiatric symptoms were reduced, the caregiver's degree of concern decreased, and the depressive symptoms of both were reduced. It was found that cognitive function remained stable and that the quality of life improved (Viola, et al, 2011). McLaren, LaMantia & Callahan have developed a systematic review of the literature in which the aim was to determine whether non-pharmacological measures such as exercise, occupational therapy and other multidisciplinary interventions contribute to delayed functional decline in community-dwelling dementia patients.…”
Section: Resultsmentioning
confidence: 99%
“…This happens because of the current aging of the population and increase in the average life expectancy (Burton, et al, 2015;Kumar, et al, 2014). Alzheimer's disease and vascular dementia are the most common types of dementia (Burton, et al, 2015;Viola, et al, 2011;McLaren, LaMantia, & Callahan, 2013). The sedentary lifestyle also contributed to the decline of cognitive function, irritation, confusion, depression and fatigue (Winchestera, et al, 2013).…”
Section: Introdutionmentioning
confidence: 99%
“…Os dados dos estudos mostram que: 1) todos os trabalhos foram realizados com idosos em estágio leve da DA; 2) Apenas um estudo foi realizado em instituição de longa permanência 12 [12][13][14] . A arteterapia apareceu em apenas um estudo como intervenção principal a ser investigada 11 , porém ela também foi utilizada no estudo de Viola et al 14 como parte da reabilitação multidisciplinar empregada.…”
Section: Tratamentos Não Farmacológicos Da Doença De Alzheimerunclassified